A distant TANGO1 family member promotes vitellogenin export from the ER in C. elegans - Jimmy H. Mo; Chao Zhai; Kwangsek Jung; Yan Li; Yonghong Yan; Meng-Qiu Dong; Ho Yi Mak (iScience)
Summary: Vitellogenin is thought to share a common ancestor with human apolipoprotein B (ApoB) for systemic lipid transport. In Caenorhabditis elegans, although a general route for inter-tissue vitellogenin transport has been described, the full mechanism that underlies its intracellular trafficking within the intestine remains obscure. In humans, the TANGO1 family of proteins generates membrane carriers to accommodate bulky ApoB-containing lipoprotein particles for their endoplasmic reticulum (ER) export. TANGO1 orthologs have hitherto been discovered in most metazoans, except nematodes. Here, we report the C. elegans TNGL-1 as a mediator of vitellogenin export from the ER. Depletion of TNGL-1 causes the retention of vitellogenin in the ER lumen. Furthermore, the TNGL-1 C-terminal unstructured domain and its luminal globular domain are required for its proper localization and cargo engagement, respectively. Our findings support TNGL-1 as a distant TANGO1 family member and point to the universal requirement of TANGO1-based mechanisms for the secretion of specific metazoan proteins.